The Effect Of The Project Based Learning Model Using Audio Visual Media On The News Text Writing Skills Of Grade XI - Nasif Maruli Sinaga; Immanuel Doclas Belmondo Silitonga (STABN RADEN WIJAYA WONOGIRI, 2025)
This study aims to determine the effect f the Project-Based Learning model using audio-visual media n the news writing skills f eleventh-grade students at SMA Swasta Teladan Pematangsiantar. The background f this study is the students' low news writing skills, which are caused by a lack of understanding f the structure and rules f news writing, such as the placement f the 5W+1H elements. Students practice writing news texts rarely, resulting in a lack of familiarity with the correct style and format. This study used a quantitative approach with a pre-experimental method and a ne-group pretest-posttest design. The sample consisted of 40 students in grades XI-5, selected using a purposive sampling technique. The instrument used was a news writing test before and after the implementation of the project-based learning model using audio-visual media. The results showed a significant improvement in students' news writing skills after the implementation of the project-based learning model using audio-visual media, as evidenced by the difference in pre-test and post-test scores. Audio-visual media has proven effective in improving important aspects of news writing. Thus, the project-based learning model using audio-visual media can be an innovative learning alternative to improve students' writing skills.